Non-invasive diagnosis of advanced fibrosis and cirrhosis - Sharma, Suraj (World J Gastroenterol, 2014)
Liver cirrhosis is a common and growing public health problem globally. The diagnosis of cirrhosis portends an increased risk of morbidity and mortality. Liver biopsy is considered the gold standard for diagnosis of cirrhosis and staging of fibrosis. However, despite its universal use, liver biopsy is an invasive and inaccurate gold standard with numerous drawbacks. In order to overcome the limitations of liver biopsy, a number of non-invasive techniques have been investigated for the assessment of cirrhosis. This review will focus on currently available non-invasive markers of cirrhosis. The evidence behind the use of these markers will be highlighted, along with an assessment of diagnostic accuracy and performance characteristics of each test. Non-invasive markers of cirrhosis can be radiologic or serum-based. Radiologic techniques based on ultrasound, magnetic resonance imaging and elastography have been used to assess liver fibrosis. Serum-based biomarkers of cirrhosis have also been developed. These are broadly classified into indirect and direct markers. Indirect biomarkers reflect liver function, which may decline with the onset of cirrhosis. Direct biomarkers, reflect extracellular matrix turnover, and include molecules involved in hepatic fibrogenesis. On the whole, radiologic and serum markers of fibrosis correlate well with biopsy scores, especially when excluding cirrhosis or excluding fibrosis. This feature is certainly clinically useful, and avoids liver biopsy in many cases.